Application of flexible housing for a selected socialized housing project in Quezon City An exploratory study - Gatus, Courtney C.; Mayo, Adelaida V. (Quezon City College of Home Economics, University of the Philippines Diliman, 2016)
Using a multiple case study approach, this thesis sought to examine how the application of the concept of flexibility in the interiors of selected housing units in Bistekville II, a socialized housing project in Quezon City, may be beneficial to its users. The objectives of the study include the following: (1) To describe the interior design of the housing units; (2) To identify the various spatial needs and preferences of the users; (3) To analyze whether the application of the concept of flexibility address the users' needs; and (4) To propose recommendations for the improvement of the interior design of future government housing units following the principle of flexibility. Using purposive sampling, the researcher identified Bistekville II as the socialized housing project to be included in the study. Snowball sampling was used to select six housing units in Bistekville II belonging to two types namely, Rowhouse and Multi-Storey Row Building, as the samples of the study, represented by a member of each of the households. Tools for data-gathering include observation guide, a digital camera, a questionnaire and interview guide. Data were analyzed using the three pillars of sustainability, namely social and economic development, and environmental protection, to assess whether the housing units were able to cater to and satisfy the families present and future needs. Results showed that Filipino values have a strong bearing on the priorities of the respondent families with regards to the use of the areas in their housing units. Findings suggest that the interior design of the housing units in Bistekville II allowed a certain degree of flexibility in terms of the finishes and layouts, but none for future expansion. The researcher recommends better programming of the interior spaces of future housing units with consideration for flexibility, which may help these projects achieve a holistic sustainability for the families.
Submitted June 2016.
Thesis (BS Interior Design)--University of the Philippines Diliman.
Keywords: Public housing -- Philippines -- Quezon City -- Interior decoration